2016
DOI: 10.1002/anie.201603698
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Silica Particles Integrated with All‐Inorganic CsPbBr3 Perovskite Quantum‐Dot Nanocomposites (MP‐PQDs) with High Stability and Wide Color Gamut Used for Backlight Display

Abstract: All-inorganic CsPbX3 (X=I, Br, Cl) perovskite quantum dots (PQDs) have been investigated because of their optical properties, such as tunable wavelength, narrow band, and high quantum efficiency. These features have been used in light emitting diode (LED) devices. LED on-chip fabrication uses mixed green and red quantum dots with silicone gel. However, the ion-exchange effect widens the narrow emission spectrum. Quantum dots cannot be mixed because of anion exchange. We address this issue with a mesoporous PQD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
395
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 760 publications
(418 citation statements)
references
References 27 publications
8
395
1
3
Order By: Relevance
“…Very recently, we and others have demonstrated that the encapsulation of perovskite NCs in a polyhedral oligomeric silsesquioxane matrix or a mesoporous silica shell not only prevents this halide exchange, but also enhances the water resistivity of the NCs. [122][123][124][125] In addition, perovskite NCs are extremely sensitive and tend to degrade or transform in to other compounds (such as metallic lead) under exposure to electron beams. 25 The exact mechanisms of these transformations need to be investigated, as TEM studies are crucial for unambiguous characterization of the morphology of perovskite NCs.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, we and others have demonstrated that the encapsulation of perovskite NCs in a polyhedral oligomeric silsesquioxane matrix or a mesoporous silica shell not only prevents this halide exchange, but also enhances the water resistivity of the NCs. [122][123][124][125] In addition, perovskite NCs are extremely sensitive and tend to degrade or transform in to other compounds (such as metallic lead) under exposure to electron beams. 25 The exact mechanisms of these transformations need to be investigated, as TEM studies are crucial for unambiguous characterization of the morphology of perovskite NCs.…”
Section: Discussionmentioning
confidence: 99%
“…(c) Photostability test of MP-CsPbBr 3 and CsPbBr 3 . Adapted from ref (104). Copyright 2016, Wiley Online Library.…”
mentioning
confidence: 99%
“…Wang et al used commercially available mesoporous silica mixed with green CsPbBr 3 NCs 104 to similarly bestow water resistance and prevent ion exchange in their mixtures of different composition. The photostability comparison is shown in Figure 7c.…”
mentioning
confidence: 99%
“…[1] As an ovel promising optoelectronic material, they can be used in light-emitting diodes (LED), lasing, photodetection, and backlight display. [3] Kanaras et al reported that the poly (maleicanhydride-alt-1-octadecene) (PMA) was integrated into the synthesis of the PQDs,the chemical and optical stability as well as processability was improved. This challenge has motivated many efforts,a nd remarkable progresses have been achieved by several groups in the recent years.L iusg roup prepared mesoporous silica PQDs nanocomposite,which exhibited better photostability and thermal stability.…”
mentioning
confidence: 99%
“…[10] These findings naturally inspired us to think about the idea of SiO 2 /Al 2 O 3 binary coating for PQDs.Actually,the SiO 2 /Al 2 O 3 binary coating has been already proved of providing better protection than the individual coating, for various materials,s uch as steel, [11] graphite, [12] and laser anti-damage material. "Di-sec-butoxyaluminoxytriethoxysilane (DBATES,( sec-BuO) 2 -Al-O-Si(OEt) 3 )" was chosen here as the single molecular precursor for SiO 2 /Al 2 O 3 matrix, which contains two alkoxide functionalities and at ypical Al-O-Si linkage. [14] Here,w es uccessfully incorporated CsPbBr 3 QDs into aS iO 2 /Al 2 O 3 monolith through as imple sol-gel process in toluene,a nd obtained ar obust luminescent QDs-SiO 2 /Al 2 O 3 monolith (QDs-SAM) with surprising high stability and PLQY (90 %).…”
mentioning
confidence: 99%